Bibliography of the Journal Women's World: Journal of Serbian Women's Charity Associations Part II (1886-1890) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Women's World: Journal of Serbian Women's Charity Associations was edited by Arkadije Varadjanin since 1886 until 1914. This is the second part of the Bibliography which refers to the four years of publication (1891-1894) and contains 631 bibliographical units described de visu.